Adrenal C11-oxy C21 steroids contribute to the C11-oxy C19 steroid pool via the backdoor pathway in the biosynthesis and metabolism of 21-deoxycortisol and 21-deoxycortisone. Issue 174 (November 2017) - Barnard, Lise; Gent, Rachelle; van Rooyen, Desmaré; Swart, Amanda C.
Graphical abstract: Highlights: Adrenal CYP11B isozymes catalyze the 11β-hydroxylation of 17α-hydroxyprogesterone. 11βHSD1 and 11βHSD2 convert 21-deoxycortisone (21dE) and 21-deoxycortisol (21dF). SRD5A catalyzes the conversion of 21dF and 21dE to 11OHPdione and 11KPdione. AKR1C2 reduces the C3-hydroxyl moiety in the biosynthesis of 11OHPdiol and 11KPdiol. 11OHPdiol and 11KPdiol are lysed by CYP17A1, yielding 11OHAST and 11KAST. Abstract: 21-Hydroxylase deficiency presents with increased levels of cytochrome P450 21‐hydroxylase substrates, progesterone and 17α-hydroxyprogesterone, which have been implicated in the production of androgens via the backdoor pathway. This study shows the biosynthesis of C11-oxy C21 steroids, 21-deoxycortisol and 21-deoxycortisone, and their metabolism by steroidogenic enzymes in the backdoor pathway yielding novel steroid metabolites: 5α‐pregnan-11β, 17α-diol-3, 20-dione; 5α-pregnan-17α-ol-3, 11, 20-trione; 5α‐pregnan-3α, 11β, 17α-triol-20-one and 5α-pregnan-3α, 17α-diol-11, 20-dione. The metabolism of 21-deoxycortisol was validated in LNCaP cells expressing the relevant steroidogenic enzymes showing for the first time that the steroid, produced at high levels in 21OHD, is metabolised via the C11-oxy derivatives of 5α‐pregnan-17α-ol-3, 20-dione and 5α‐pregnan-3α, 17α-diol-20-one to substrates for the lyase activity of CYP17A1, leading to the production of C11-oxy C19 steroids. 21-Deoxycortisol thus contributes to the pool of potent androgens in 21OHD, with novel steroid metabolites also presenting possible biomarkers in disease identification.